Shoah pornography: the Stalag phenomenon in Israel during the 1960s - Spiegel, Jasmin; Dekker, Arne; Briken, Peer; Gomille, Anika; Rettenberger, Martin (Frontiers in Psychology, 2025)
The ‘Stalags’ (Orig. ‘Stalagim,’ Abbr. German = ‘Stammlager’) are soft pornographic booklets portraying a sadomasochistic plot at the time of Shoah. The aim of this study is to investigate the psychological and sociocultural causes of this phenomenon in Israel during the 1960s. To this end, five expert interviews were conducted and evaluated using a qualitative content analysis. In total, six categories were extracted, which provided the basis for a discussion of the popularity and spread of Stalags during the Adolf Eichmann trial in Israel. First, reversal of hatred of antisemitic images of Jews; second, sexuality as a political category; third, defense of traumatic guilt by sexualization; fourth, sexuality as a practical category using feelings of power leading to sexual arousal; fifth, reflection of the new idea of masculinity (‘The Sabra’) in society; and sixth, the influence of American Hollywood cinema on aesthetics and plot. These categories were enriched using psychoanalytic theory.